Shoe Product Marketing Strategy Using SWOT Analysis Method with IFAS and EFAS Matrices at PT. Bagoes Tjipta Karya - syafaat; Wahid, Abdul (Journal Knowledge Industrial Engineering (JKIE), 2024)
The marketing strategy of shoe products at PT. Bagoes Tjipta Karya was analyzed using the SWOT method with the IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) matrix approaches. This research aims to identify internal and external factors that affect the competitiveness of companies in the midst of increasingly fierce competition in the shoe industry. Data was collected through observation, interviews, and documentation studies, then analyzed by giving weight and rating to each factor. The results of the study show that the company's main strength lies in its business-friendly working principles, a simple bureaucratic system, and competitive production prices. Meanwhile, the weaknesses include less than optimal digital promotion and low quality of human resources. Externally, opportunities such as potential markets and high industrial growth must be taken advantage of, while threats such as local competition and fluctuations in raw material prices need to be addressed. Based on the analysis, the company is in a stable growth strategy position, with strategic recommendations such as increasing production capacity, improving digital promotion, and strengthening the marketing network. These findings make a practical contribution to the development of adaptive marketing strategies for the local shoe industry.